Digital Financial Literacy and Financial Inclusion in Indonesia’s Digital Economy - Prihandini, Wiwiek (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The digital economic transformation in Indonesia has expanded public access to financial services through the development of fintech, digital banking, and electronic payment systems. However, this increased access has not been matched by a corresponding ability to understand and manage digital financial risks. This study aims to analyze the current condition of digital financial literacy (DFL) in Indonesia, the challenges that hinder digital financial inclusion, and strategies for strengthening DFL policies. Using a qualitative descriptive approach based on literature and document analysis, this research draws on data from Financial Services Authority and Central Statistics Agency (SNLIK 2024–2025), Bank Indonesia, AFTECH, as well as literature from the OECD, World Bank, and IMF. The findings reveal that although financial inclusion has reached 80.51%, the DFL rate remains relatively low (around 54–56%), creating a gap between digital access and financial capability. Social and behavioral factors, combined with weak inter-agency coordination, exacerbate online fraud risks and erode public trust. Therefore, enhancing DFL requires cross-institutional policies, integration of digital literacy into the national financial inclusion strategy, and community-based financial education programs. Improving DFL is key to building a secure, inclusive, and equitable digital financial ecosystem that supports Indonesia’s sovereign digital economy. Keywords: digital financial literacy, financial inclusion, digital economy, financial behavior, Indonesia